2001
DOI: 10.1034/j.1600-0633.2001.100401.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology and habitat of the threespine stickleback, Gasterosteus aculeatus microcephalus, in a remnant population of northwestern Baja California, México

Abstract: – The feeding ecology and habitat of the threespine stickleback (Gasterosteus aculeatus microcephalus Girard, 1854) was studied from November 1996 to May 1997 in a remnant population of northwestern Baja California, México. The analysis of the stomach content of 179 individuals (25 to 56 mm standard length [SL]) showed a diet dominated by cyclopoid copepods (43.8%) and chironomid larvae (39.1%). Diet in relation to size and sex of the fish was dominated by copepods in autumn and winter and by chironomid larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…Thus, this study confirms previous research indicating that three-spine stickleback feeds almost exclusively on aquatic invertebrates (Sánchez-Gonzáles et al, 2001;Copp & Kovác, 2003). Actually, results of trait analysis in this study are in accordance with the bottom-feeder behaviour found in previous studies (Ranta & Kaitala, 1991;Hart, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, this study confirms previous research indicating that three-spine stickleback feeds almost exclusively on aquatic invertebrates (Sánchez-Gonzáles et al, 2001;Copp & Kovác, 2003). Actually, results of trait analysis in this study are in accordance with the bottom-feeder behaviour found in previous studies (Ranta & Kaitala, 1991;Hart, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Körner and Dugdale (2003) showed a switch of fish to periphyton-scraping invertebrates at low zooplankton abundance. In our experiment, in all countries except Greece, we used sticklebacks, a bottom-feeder that essentially feeds on plankton and benthic prey (Sánchez-Gonzáles et al 2001). However, periphyton biomass was highest in Greece where mosquitofish were used instead of sticklebacks.…”
Section: Discussionmentioning
confidence: 99%
“…C ranges from 0 (no habitat overlap) to 1 (full habitat overlap). Overlap is generally considered significant when C exceeds or equals 0.60 (Zaret and Rand, 1971;Sµnchez-Gonzµles et al, 2001). Microhabitat types were defined as all possible combinations of depth (two categories, i.e.…”
Section: Discussionmentioning
confidence: 99%